The fugu plan the untold story of the Japanese and the Jews during World War Two - Tokayer, Marvin 1936- (Weatherhill, 1996)
This book discusses the Fugu Plan, a plan virtually unheard of when this book was first published in 1979. That short-lived plan was personified by Chiune Sugihara. From November 1939 to September 1940, Sugihara was officially the Japanese consul in Kovno (or 'Kaunas'), Lithuania. In reality, Sugihara had been sent to Kovno to gather intelligence about Soviet and German troop movements in the area. Because he was there, however, and because of who he was, Sugihara became one of the crucial players in the fugu plan--a scheme that, by the war's end, would save the lives of thousands of Jews, as well as the entire Mir Yeshiva, whose scholars would survive to inspire a new era of Jewish learning in the U.S. and Israel.